Impact of Government Policies on The Competitiveness of Soybean Farming System in Indonesia: Study in Bangsalsari District, East Java Province - Haryanto, Tri; Kurniawan, Andri (Universitas Airlangga, 2019)
Soybean farming in Indonesia, as well as in other countries in the world, has an important role in providing food for the population, food ingredients for the food and beverage industry, and feed ingredients. Some policies have been implemented by the government to increase the profitability, efficiency and competitiveness of soybean farming. This study used the Policy Analysis Matrix (PAM) method to assess the competitiveness of soybean farming and evaluate the effectiveness of government policies in soybean farming. The results showed that soybean farming had a competitive advantage and comparative advantage. The results of the sensitivity analysis indicate that output price policy is an effective instrument to increase the profitability and competitiveness of soybean farming in Indonesia.Keywords: Government policy, Competitiveness, Sensitivity analysis, PolicyAnalysis MatrixJEL Classification: Q1, Q18